1990
DOI: 10.1017/s0950268800059495
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory analysis of winds and vesicular stomatitis in North America, 1982–5

Abstract: SUMMARYOutbreaks of vesicular stomatitis, serotype New Jersey, during epidemics in the United States and northern Mexico, 1982–5, were examined by backward trajectories of winds to investigate spread and possible sources. The outbreaks selected for analysis did not involve introduction of disease by infected animals. The findings indicate that wind could have been responsible for carrying infection from northern Mexico to Arizona and New Mexico and thence to Colorado and Utah and on to Wyoming, Idaho and Monta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…since hundreds of thousands of cattle are imported every year mostly into Texas without reports of clinical outbreaks. It has been suggested that infected insects originating in enzootic areas of Mexico could be carried by wind into the southern United States (Sellers and Maarouf, 1990). If this was the case, we should expect more cases reported in Northern Mexico prior to or during United States epizootics which has not been the case.…”
Section: Discussionmentioning
confidence: 97%
“…since hundreds of thousands of cattle are imported every year mostly into Texas without reports of clinical outbreaks. It has been suggested that infected insects originating in enzootic areas of Mexico could be carried by wind into the southern United States (Sellers and Maarouf, 1990). If this was the case, we should expect more cases reported in Northern Mexico prior to or during United States epizootics which has not been the case.…”
Section: Discussionmentioning
confidence: 97%
“…Thi s is based on the seasonal incidence of epidemics, the scattered distribution of affected premises, the rapidity of spread and its association with pastures, waterways, humid conditions and wind currents (Mason 1978;Monath et a/. 1986;Sellers and Maarouf 1990).…”
Section: Epidemic Regionsmentioning
confidence: 99%
“…Thi s Is based on the seasonal Incidence of epidemics, the scattered distribution of affected premises, the rapidity of spread and its assoclatlon with pastures, waterways, humid conditions and wind currents (Mason 1978;Monath et a/. 1986;Sellers and Maarouf 1990).…”
Section: Aetiologymentioning
confidence: 99%